Geospatial enablement to facilitate urban planning commitment on urban resilience in Malaysia - Hj. Mohd. Noor, Norzailawati; Ibrahim, Illyani; Mohd Nor, Marina (PLANMalaysia, Ministry of Housing and Local Government, 2021)
Cities are vulnerable to a range of hazards and shocks. The COVID-19 has exposed the direct consequences of limited preparedness and resilience when facing a global emergency. In the face of these growing challenges, cities need the tools and knowledge to plan and mitigate the adverse impacts. The geospatial approach can play a critical role in supporting a more resilient urban planning with meaningful decision-making. Thus, this paper highlights the extent to which emerging geospatial approaches have deliberately enabled urban planning efforts to achieve urban resilience in Malaysia. To do so, we conduct a systematic literature review on different fields, and aspects of the geospatial components which consist of Geographical Information System (GIS), Remote Sensing (RS) and other relevant ones. The finding shows that moderate progress has been made on providing and exploring geospatial data usage by the relevant agencies to include geospatial data in various urban applications in Malaysia. Finally, this paper informs the industry, governmental and non-governmental and academia on geospatial enablement progress. Simultaneously, we believe that this tool to assist in urban applications is among the best promising ones for future sustainability and resiliency of cities.